Rekayasa Aplikasi Pengelolaan Pencarian Referensi Skripsi Berformat PDF (Portable Document Format) Berbasis Website - Mukhsin, Mukhsin; Darsanto, Darsanto; Ilyas, Aji Maulana (Department of Computer Engineering, Universitas Wiralodra, 2025)
Currently, many thesis documents are still stored in physical form at university libraries, making it difficult for students to find references efficiently. This study aims to develop a web-based application that can manage and search thesis documents in PDF format. The system uses a combination of PHP Native for the interface, MySQL for data storage, and Python for extracting metadata from PDF documents. The search feature is built using a keyword-based matching technique that helps match user queries with document titles. The system was developed using the V-Shape model of the Software Development Life Cycle (SDLC) and tested using Black Box Testing and the System Usability Scale (SUS) method. The results showed that the application met user needs, improved search efficiency, and provided an accessible and structured interface. This system is expected to support academic environments, particularly within university faculties, in managing and retrieving digital references effectively.